ANALYSIS OF THE TRANSITION FROM PASSIVE TO ACTIVE IMMUNITY IN HOLSTEIN CALVES USING SERIAL HEMATOLOGICAL SAMPLES (REMUNOM, 2026)
The aim of this study was to evaluate the variation of reactive lymphocytes, total leukocytes, and absolute lymphocytes over 56 days, in order to understand the dynamics of the cellular immune response and the possible transition from passive to active immunity. The experimental design consisted of serial blood collections on different days (7th, 14th, 21st, 28th, 35th, 42nd, 49th, and 56th day), with hematological analysis and application of the Scott-Knott clustering test to detect statistical differences (p < 0.05). A progressive increase in reactive lymphocytes was observed, peaking on day 35, suggesting the moment of highest activation of the adaptive immune response. Total leukocytes and absolute lymphocytes reached their maximum values on day 49, reinforcing the occurrence of a consolidated immune response. These findings suggest indirect hematological evidence possibly associated with the process of immune adaptation during the first weeks of life.